Risk Taking in Asymmetric Tournaments - Matthias Kräkel; Dirk Sliwka (University of Bonn, Bonn Graduate School of Economics (BGSE), 2001)
In an asymmetric tournament model with endogenous risk choice by the agents it is shown that equilibrium efforts decrease (increase) with risk if abilities are sufficiently similar (different). Risk also affects winning probabilities. The interaction of both effects is analyzed.
Keywords: D23; J3; M12; 330; effort effect; likelihood effect; risk taking; tournament